Add-on effect of Guizhi Fuling formula to mifepristone for endometriosis: A meta-analysis of randomized controlled trials. Issue 33 (August 2019) - Meng, Wenbin; Ta, Na; Wang, Fei
Abstract: Background: Guizhi Fuling pill, a famous traditional Chinese herbal formula, has been widely used for treatment of gynecological diseases. This meta-analysis sought to evaluate the add-on effect of Guizhi Fuling capsule (GZFL) to mifepristone in women with endometriosis. Methods: A comprehensively literature search was conducted using Pubed, Embase, Cochrane Library, Wanfang, CNKI, VIP databases from their inceptions to January 25, 2019. Randomized controlled trials that compared GZFL plus mifepristone to mifepristone alone for treatment of endometriosis were eligible. Main outcomes were pregnancy, reduction of the recurrence, and serum level of follicle-stimulating hormone, luteinizing hormone, estradiol or progesterone. Results: A total of 1052 women with endometriosis from 10 trials were identified and analyzed. Meta-analyses showed that GZFL plus mifepristone was superior to mifepristone in reducing the recurrence of endometriosis (RR 0.40; 95% CI 0.27–0.59) and improving the pregnancy (risk ratio [RR] 1.74; 95% confidence intervals [CI] 1.40–2.17). Moreover, adjuvant treatment with GZFL also significantly reduced serum level of estradiol (mean difference [MD] −20.83 pmol/L; 95% CI −34.01 to −7.65) and progesterone (MD −0.18 mmol/L; 95% CI −0.23 to −0.12). However, there were no significant differences in serum level of follicle-stimulating hormone (MD −0.42 U/L; 95% CI −1.16 to 0.31) and luteinizing hormone (MD −0.04 U/L; 95% CI −0.43 to 0.34). Conclusion: GZFL as adjuvant therapy to mifepristone appears to have additional benefits in preventing recurrence of endometriosis and improving pregnancy among women with endometriosis. However, these conclusions should be interpreted with caution due to the methodological flaws of the included trials.